Hall current effects on a fully developed combined convection flow in a vertical channel: A study of heat transfer - Bala, A. Jyothi (Bulletin of Applied Mathematics and Mathematics Education, 2023)
This paper the effect of magnetic field on free and forced convection flow between two vertical parallel plates is studied. The flow is assumed to be steady and fully developed. The vertical walls are kept at different uniform temperatures. The expression for velocity and bulk temperature are obtained in magnetic and in non-magnetic cases. Hall current effect plays a significant role in determining the flow pattern of an incompressible, viscous, conducting fluid under the influence of an external magnetic field. The effects of magnetic parameter or Hartmann number M, ratio of wall temperature differences (rT), ratio of Grashoff number and Reynolds number , the pressure gradient and the hall parameter (m) is studied numerically on velocity and bulk temperature.